2020
DOI: 10.1002/iju5.12175
|View full text |Cite
|
Sign up to set email alerts
|

Successful pembrolizumab treatment in a patient with metastatic urothelial carcinoma and underlying overlap syndrome involving systemic sclerosis and systemic lupus erythematosus

Abstract: Introduction The safety and efficacy of pembrolizumab administration in patients with urothelial carcinoma and underlying autoimmune disease (including overlap syndrome) is unknown. Case presentation We present the case of a 67‐year‐old woman with cT3N2M0 metastatic renal pelvic cancer who had been treated with prednisolone for overlap syndrome involving systemic sclerosis and systemic lupus erythematosus for 20 years. She had a remarkable response to pembrolizumab as a third‐line systemic therapy, wherein the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Clinical incidence: A total of eleven cases of lupus erythematosus were reported with anti-PD-1 therapy. Six cases were reported with pembrolizumab [121][122][123][124] and five with nivolumab 113, 125-127 immune checkpoint inhibitors. Histological and clinical diagnosis of lupus erythematosus and lichenoid reactions in some cases is difficult to differentiate 113 .…”
Section: Pathogenesismentioning
confidence: 99%
“…Clinical incidence: A total of eleven cases of lupus erythematosus were reported with anti-PD-1 therapy. Six cases were reported with pembrolizumab [121][122][123][124] and five with nivolumab 113, 125-127 immune checkpoint inhibitors. Histological and clinical diagnosis of lupus erythematosus and lichenoid reactions in some cases is difficult to differentiate 113 .…”
Section: Pathogenesismentioning
confidence: 99%
“…Pembrolizumab is a standard therapy for patients with platinum‐based chemotherapy‐resistant urothelial carcinoma 1 . Although pembrolizumab administration for patients with preexisting autoimmune disease (AID) needs careful considerations, Kurokawa et al reported a fortunate case of advanced renal pelvic cancer who was successfully treated with third‐line pembrolizumab 2 . They also reported the potential role of monitoring of AID titer (anti‐nuclear antibody and centromere antibody) during treatment for management.…”
mentioning
confidence: 99%
“…They also reported the potential role of monitoring of AID titer (anti‐nuclear antibody and centromere antibody) during treatment for management. However, an indication of immunotherapy needs to be careful consideration because 23–38% of patients with preexisting AID experienced flares in other cancers, especially in patients with symptomatic AID (up to 50%) 2,3 . Furthermore, the optimal dose of maintenance corticosteroids during immune‐oncologic therapy remains unclear.…”
mentioning
confidence: 99%